Structure and Electrochemical Impedance of LiNi\(_{x}\)Mn\(_{2 - x}\)O\(_{4}\) - Anh Tan, Ta; Si Hieu, Nguyen; Ha Chi, Le; Tran Chien, Dang; Dinh Trong, Le; Duy Long, Pham (Communications in Physics, 2017)
Ni-substitution spinel LiNixMn2−xO4 (x = 0, 0.1, 0.2) materials were synthesized by the sol--gel method. The structure and morphology of the samples were characterized by the X-ray diffraction (XRD) and the scanning electron microscopy. The ac conduction of the materials was investigated by electrochemical impedance spectroscopy (EIS) measurements. The refinement results showed that the substitution of Ni decreased the lattice constant and Mn--O distance, while increased Li--O bond length and 16c octahedral volume. The EIS results confirmed the decrease of conductivity with increasing Ni substitution content. Based on XRD and EIS results, the relationship between the crystal structure and electrochemical behavior of the materials was discussed and explained.